Sustainability of Slum-Free Outcomes: Assessing Legal Durability and Administrative Capacity in Decentralized Central Java - Martitah Martitah; Saru Arifin; Natal Kristiono; Tegar Islami Putra; Nizam Alfarisi (Universitas Negeri Semarang, 2026)
The elimination of all slums in Indonesia was specified in the country's National Development Plan for 2015-2019. This program sought to realize the UN-HABITAT City Without Slums (CWS) goal within the framework of the Millennium Development Goals (MDGs). In accordance with the objective of the CWS, this case study focuses on Central Java, one of Indonesia's decentralized governments with a significant slums issue. This article argues that implementing CWS (‘Kota Tanpa Kumuh’-KOTAKU) under decentralized government parallels the nation's early slum eradication initiatives, which primarily focused on the physical program and lacked the difficulties associated with slums. The partial success of the KOTAKU program is attributable to the limited government initiatives in slums. In this case, the local regulation (Peraturan Daerah, Perda) and the slums budget are the critical factors limiting the local government intervention. With library research method, this research proposes incorporating private enterprises, non-governmental organizations, and universities into slum improvement programs.